Evaluation of Site Effects in Hong Kong - J.W. Pappin; R.C.H. Koo; M.W. Free; H.H. Tsang (Electronic Journal of Structural Engineering, 2008)
This paper describes an investigation into the potential seismic site response effects for the ground conditions in Hong Kong. A site classification map for the Hong Kong region has been produced using current IBC site classes. Published geological maps and detailed ground investigation information have been used for the classification. One-dimensional site response analyses have been carried out to determine how various representative types of site profiles of Hong Kong will potentially respond to earthquake ground motion. The response of soil profiles was investigated using three input earthquake ground-motion levels corresponding to bedrock motion with 50%, 10% and 2% probability of being exceeded in 50 years. The results are presented in terms of spectral ratios for the different Site Classes. A simplified manual procedure for rapid assessment of site response effects has been developed by the University of  Hong Kong to produce displacement- based design response spectra. There are extensive areas of reclamation in Hong Kong and the potential for liquefaction in these areas, and other areas underlain by non-cohesive, saturated soils, was considered sufficiently high to warrant investigation. The methodology and results of a liquefaction assessment are presented in the final part of this paper